Icons of war photography : how war photographs are reinforced in collective memory : a study of three historical reference images of war and conflict - Gassner, Patricia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2009.